Anti-VEGF Therapy In Central Retinal Vein Occlusions - Rahmah, Meidina; Amin, Ramzi; Ansyori, AK (International Journal of Retina, 2018)
Introduction: Central retinal vein occlusion (CRVO) is the second most common retinal vascular disease after diabetic retinopathy and is estimated to affect more than 16 million adults worldwide. Treating the underlying cause of occlusion of the central retinal vein, reducing the risk factors, and early and proper management are the keys toward a better prognosis in patients with CRVO. Repeated frequent treatment of CRVO with macular edema with intravitreal anti-vascular endothelial growth factor (anti-VEGF) is an effective treatment to improve visual outcome. In this case report we assess the 3-month efficacy of anti-VEGF therapy in CRVO. Method: In this case, a 52-year-old man presented with an acute loss of vision over the last week in his left eye. His baseline visual acuity was 1/60 and his central retinal thickness (CRT) on Optical Coherence Tomography (OCT) was 523 Î¼m. Fundus examination revealed a hemorrhage in all four quadrants, hard exudates, swelling of the optic nerve, and macular edema. Laboratory test confirms hyperlipidemia and we consult this patient to Internal Medicine Department. This patient got 3 monthly injections of 1,25 mg Bevacizumab. Results: By 3 months, the OCT appeared fairly normal and the visual acuity improved to 6/60 Conclusion: Anti-VEGF therapy is effective for treating macular edema secondary to CRVO